The Bedford Guide for College Writers with Reader - J. Kenedy X. (Bedford, 2007)
X.J. KENNEDY is an acclaimed poet, children's author, college teacher, and textbook author. He has taught freshman composition at the University of Michigan, the University of North Carolina, Greensboro, and Tufts University. Since 1966, more than 2 million students have treasured his introductory literature texts and The Bedford Reader, coedited with Dorothy M. Kennedy and Jane E. Aaron, now in its Ninth Edition.